Biodiversity in the city: key challenges for urban green space management - Aronson, Myla FJ; Lepczyk, Christopher A; Evans, Karl L; Goddard, Mark A; Lerman, Susannah B; MacIvor, J Scott; Nilon, Charles H; Vargo, Timothy (Frontiers in ecology and the environment, 2017)
Cities play important roles in the conservation of global biodiversity, particularly through the planning and management of urban green spaces (UGS). However, UGS management is subject to a complex assortment of interacting social, cultural, and economic factors, including governance, economics, social networks, multiple stakeholders, individual preferences, and social constraints. To help deliver more effective conservation outcomes in cities, we identify major challenges to managing biodiversity in UGS and important topics warranting further investigation. Biodiversity within UGS must be managed at multiple scales while accounting for various socioeconomic and cultural influences. Although the environmental consequences of management activities to enhance urban biodiversity are now beginning to be addressed, additional research and practical management strategies must be developed to balance human needs and perceptions while maintaining ecological processes.